Effective treatment of hydroplasty injections and immediate physical therapy for glenohumeral adhesive capsulitis: a retrospective clinical analysis - Austin J. Koenig, BA; Evan P. Shoemaker, BA; Rebecca Stone McGaver, MS, ATC; Ayush D. Shah, BA; James A. Palmer, DPT; Allan F. Hunt, MD (JSES International)
Background: Currently, limited research exists evaluating the effectiveness of physical therapy (PT) in conjunction with a hydroplasty procedure for the treatment of adhesive capsulitis. The purpose of this study is to demonstrate the immediate and short-term effects of hydroplasty with an intensive PT regimen on patients with adhesive capsulitis by comparing preprocedural and postprocedural range of motion (ROM) and overall shoulder function. Methods: A retrospective chart review initially identified 187 patients and 194 shoulders who received hydroplasty treatment for adhesive capsulitis, of those, 182 patients and 189 shoulders were included in our analysis. The preprocedural and postprocedural ROM included forward flexion, abduction, internal rotation, external rotation (ER) at 90, and ER at side. These ROMs were again checked at the end of the patients' PT regimen. Variables recorded included demographics, autoimmune and/or thyroid disorders, diabetes, and smoking status. The frequency and quantity of PT visits were recorded to assess the combined impact of time elapsed and PT on ROM following a hydroplasty procedure. Reinjections and further surgical intervention were also recorded. Results: A total of 182 patients, for 189 shoulders, were included in the study for data analyses. Dependent, 2-tailed paired t-test analysis showed a statistically significant increase in ROM in forward flexion, abduction, internal rotation, ER at side, and ER at 90 (P value < .001). Patients attended PT for an average of 9.54 visits and an average of 6.30 weeks. Postprocedurally, 19 patients experienced further intervention: 9 patients received subsequent corticosteroid injections: 8 had recurrent hydroplasty procedures, 1 had nonresolving adhesive capsulitis, and 1 received a concomitant hydroplasty with arthroscopic release. Conclusion: Hydroplasty followed by PT can provide significant improvements in ROM to patients with adhesive capsulitis. Adding immediate aggressive and continued PT suggests this treatment plan is a reproducible option when looking to address and shorten the duration of symptomatic adhesive capsulitis.